The influence of substrates and triple superphosphate on the growth of rangpur lime till the first transplanting - Cambraia, José Ferreira (Pesquisa Agropecuaria Brasileira, 2014)
This research was conducted in May 1977 at the Escola Superior de Agricultura de Lavras (ESAL). Minas Gerais, to study the influence of substrates and triple superphosphate on the growth of rangpur lime. The experimental design used was a randomized block with a 4 x 4 factorial scheme and three replicates. The four substrates were: washed sand; top layer Rust Dystrophic Latosol; mixture of 1/3 sand and 2/3 soil; mixture of 1/3 sand and 2/3 soil. The four levels of triple superphosphate were 0,50, 100, 150 g per subplot. The substrate greatly affected the rangpur lime (Citrus limonia Osbeck) growth. Independently from substrates, those treatments that did not receive triple superphosphate were slow in growth. The substrates with 2/3 clay and 1/3 sand together with 150 g triple superphosphate presented 250% of total dry weight of seedling comparing with those treatments without receiving superphosphate.